Peningkatan Akses Penyimpanan Data Client Menggunakan Website Pada Inside Lombok - Ahmad Ahmad; Habib Ratu Perwira Negara; I Nyoman Darmawan Setiaji (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2021)
The service on improving access to client data storage using the website at Inside Lombok is carried out so that data storage can be carried out effectively and efficiently. With this web, it is hoped that it will make it easier for Lombok insiders to enter and access client data wherever they are. The purpose of this activity is the development of a client database information system in Inside Lombok so that it can be accessed easily and can be done anywhere. The types of this activity are manufacture and training. This activity was carried out for 20 days with Inside Lombok employee participants. The evaluation carried out is divided into two. The first evaluation of the website creation that has been developed consists of a functional test and a satisfaction test, the second is an evaluation of satisfaction regarding the use of the web that has been used. The result of this activity is that the team has succeeded in creating a website to store client data so that Inside Lombok employees do not need to use excel anymore, which is where this website can save time for employees who want to enter client data because the format for entering data already exists and can be accessed anywhere.